PELATIHAN KEAMANAN SISTEM INSTALASI KABEL TANAM DI DESA MELINGGIH KECAMATAN PAYANGAN-GIANYAR - Budiastra, I.N.; Partha, C.G.I.; Arjana, I.G.D.; Swamardika, I.B.A. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana MengabdiDO - 10.24843/BUM.2018.v17.i01.p19, 2018)
Electricity is a very vital needs for the life of the community it is today. Electricity became the primary needs of the relatively inexpensive price because in addition is also very helpful in everyday life. In addition to electricity has huge advantages, electricity also has a hazard that can lead to accidents such as fire, electrical current was stung and damage electrical equipment. Bali is an island of the gods and the visit of a very famous Tourism both locally and internationally. The beauty of Bali we must keep together in order to look more natural. Lighting is one of the effects of the sun rays create the beauty of being a more natural look. The placement of the lights as the lighting to create a natural atmosphere, usually placed on top of or below, because the light on the object is not interrupted. Because of the Permasalahn above, then the electrical installation has also become very influential for aesthetics, so the installation is generally ditanan in the ground. The main constraint in the system in the ground is a way to install and secure the conductor. Of these problems this devotion will provide information about the security system wiring installation. Electrical hazards can be eliminated by following all electrical installation requirements. Danger of electric shock and fires can be corrected with electrical installation safety contained in the 2011 electrical installation General requirements (Amendment 2011serta year 2014 PUIL, who hinted to secure the environment in this securing human safety, mandatory use of electrical installation in accordance with the National Standard safety Indonesia (SNI). In this devotion will be given explanations and Training Security System Installation Cable plant in the village of Payangan Gianyar-Melinggih Sub-district, which provide devotion often occur because of electrical interference system wiring and equipment who do not meet the requirements of the electrical installation.